1996
DOI: 10.1097/00004647-199607000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Stimulates Activation of the Cerebral 5-Lipoxygenase Pathway during Blood-Brain Cell Contact

Abstract: The purpose of this study was to identity the trigger mechanism activating the 5-lipoxygenase pathway during blood-brain cell contact and to estimate the contribution of blood and brain cells to the cysteinyl-leukotriene (LT) biosynthesis observed under these conditions. Incubation of dissociated rat brain cells in Krebs-Henseleit solution for up to 60 min did not stimulate any detectable cysteinyl-LT biosynthesis. Incubation of recalcified rat whole blood in vitro for up to 60 min led to release of only small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…This is in analogy with results obtained with human astrocytoma tissue slices which predominantly released LTD 4 and LTE 4 and smaller amounts of LTC 4 [30]. In dissociated rat brain cells mainly LTC 4 and smaller amounts of LTD 4 have been detected [37]. The reason for the difference in HPLC profiles between cys-LT excreted in patients’ urine and rat brain tissue is the advanced degradation of the highly potent cys-LT from LTC 4 to the metabolites LTD 4 and LTE 4 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is in analogy with results obtained with human astrocytoma tissue slices which predominantly released LTD 4 and LTE 4 and smaller amounts of LTC 4 [30]. In dissociated rat brain cells mainly LTC 4 and smaller amounts of LTD 4 have been detected [37]. The reason for the difference in HPLC profiles between cys-LT excreted in patients’ urine and rat brain tissue is the advanced degradation of the highly potent cys-LT from LTC 4 to the metabolites LTD 4 and LTE 4 .…”
Section: Discussionsupporting
confidence: 86%
“…In patients suffering from vasospasm after aneurysmal subarachnoid hemorrhage significantly higher cisternal cerebrospinal fluid levels of cys-LT were observed as compared to patients without vasospasm suggesting a participation of cys-LT under these pathophysiological conditions [21, 39]. The coincubation of physiologically recalcified whole blood with autologous dissociated rat brain cells triggers a time- and volume-dependent biosynthesis of cys-LT [37]. In contrast, incubation of rat brain cells without an external stimulus is not accompanied by any detectable release of cys-LT [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microcirculation distubance is caused by thrombin generation in the brain. In addition, thrombin may directly damage nervous tissues by an increase of vascular permeability (23) and nitric oxide production in glial cells, induction of apoptosis in neurons (24) and suppression of neurite outgrowth (25). Argatroban treatment increases cerebral blood flow in ischemic brains (26,27) and is also expected to ameriolate these direct effects of thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…Nishino et al reported that thrombin infusion into the rat caudate nucleus causes increased reactive gliosis, infiltration of inflammatory cells, proliferation of mesenchymal cells, and induction of angiogenesis (8). In addition, thrombin may directly promote tissue damage in the central nervous system through an increase of vascular permeability and nitric oxide synthesis in glial cells (9). Donovanet al have shownthat thrombincauses apoptosis as evidenced by cleavage of DNA,fragmentation of nuclei, and prevention of death by inhibition of protein synthesis (10).…”
mentioning
confidence: 99%